(untitled) (Research, Society and Development, 2022)
Pregnancy is considered the period in which a woman undergoes the most physical, emotional and especially hormonal changes. In this context, caring for her health becomes fundamental in different areas of health, especially oral health. Based on this, the realization of this research starts from the following justification: It is known that the gestational period is characterized as a phase of changes and the woman is propitious for several transformations, as well as for the occurrence of diseases. This factor is linked to hormonal decline, so it is essential to monitor her health in different clinical axes. In this aspect, dental care is essential for the prevention of diseases and the diagnosis of diseases. Thus, the objective of this study focuses on: Evidencing through the literature, which is the interrelationship between pyogenic granuloma and the gestational period. To support this research, an integrative literature review was carried out, with a descriptive approach, through a survey of data in the scientific bases: LILACS, SCIELO, BRISA and MEDLINE. The emergence of pyogenic glaucoma is more common in women, especially during pregnancy, which explains this fact is the imbalance of estrogen and progesterone and increased progesterone, which contributes to the occurrence of gingival lesions during pregnancy. The increased amounts of estrogen and progesterone in the blood contribute to the growth of bacteria that are strongly associated with periodontal disease. Sex hormones can exert influence on periodontal tissue, these influences can provide tissue response and affect the composition of the dental biofilm.